2006
DOI: 10.1182/blood-2005-12-5046
|View full text |Cite
|
Sign up to set email alerts
|

The Wingless homolog WNT5A and its receptor Frizzled-5 regulate inflammatory responses of human mononuclear cells induced by microbial stimulation

Abstract: IntroductionImmunity to infections depends on the successful integration of innate and adaptive defense strategies. 1 Cells of the innate immune system, such as macrophages and dendritic cells, recognize pathogen-associated molecular patterns shared by many microbes but not found in higher eukaryotes, via members of the Toll-like receptor (TLR) family. 2,3 TLR-dependent signaling pathways can directly induce macrophage antimicrobial programs but also initiate inflammatory cell recruitment and help prime cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
340
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 323 publications
(361 citation statements)
references
References 67 publications
(78 reference statements)
18
340
2
1
Order By: Relevance
“…There is strong experimental evidence for the contribution of endogenous Wnt proteins to inflammatory cytokine responses and host defense against pathogens in in vivo models [5,11,20] as well as in a variety of cell culture systems [2,6,13,14,36]. In a model of dietinduced metabolic dysfunction, sFRP5 exerted anti-inflammatory functions in vivo, possibly by interfering with Wnt5a-induced proinflammatory cytokine production [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is strong experimental evidence for the contribution of endogenous Wnt proteins to inflammatory cytokine responses and host defense against pathogens in in vivo models [5,11,20] as well as in a variety of cell culture systems [2,6,13,14,36]. In a model of dietinduced metabolic dysfunction, sFRP5 exerted anti-inflammatory functions in vivo, possibly by interfering with Wnt5a-induced proinflammatory cytokine production [11].…”
Section: Discussionmentioning
confidence: 99%
“…IL-12 and IL-6) and chemokines (e.g. CCL2 and CCL5) by macrophages and other cell types [2,6,11,13,14]. Wnt proteins, such as Wnt5a, which signal via β-Catenin-independent pathways, including Ca 2+ mobilization, NF-κB, and MAP kinase activation, have been proposed to amplify local inflammation [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the calcium‐dependent Wnt signaling pathway, Wnt5a is thought to activate histone methyltransferase SET domain bifurcated 1, leading to the formation of a corepressor complex that suppresses peroxisome proliferator‐activated receptor γ (PPARγ) function and thus mediates the osteoblastic differentiation of mesenchymal stem cells (MSCs) 123. A recent study has demonstrated a link between Wnt5a, toll‐like receptor 4, and pathological inflammation in human macrophages 124. Furthermore, the expression of Wnt5a has been demonstrated in murine and human atherosclerotic tissue 19.…”
Section: Implication Of Noncanonical Wnt Signaling In Vcmentioning
confidence: 99%